Comportamiento de las arritmias cardiacas y los trastornos de conducción en una Unidad de Cuidados Coronarios. Characterization of cardiac arrhythmias and dysfunction of the conduction system at Intensive Coronary Care Unit. - Geovedy Martínez García; Alberto Hernández González; Nadia Sánchez Torres; Roberto Álvarez Tamayo; Alexei Suárez Rivero (ECIMED, 2011)
Introduction Cardiac arrhythmias and dysfunctions of the conduction system constitute animportant group among cardiac diseases. However, its prevalence in hospitalizedpatients has not been well established.Objective Characterization of cardiac arrhythmias and dysfunctions of the conductionsystem diagnosed in patients entered to the Coronary Intensive Care Unit ofthe Military Central Hospital "Dr. Carlos Juan Finlay".Method We conducted a descriptive study that included 222 patients entered with cardiacarrhythmias and/or dysfunctions of the conduction system between october2008 and september 2010.Results Mean age was 69,74±13,60 years, prevailing the male (54,1%) sex, and thewhite (73%) skin color. The arterial hypertension and personal antecedents ofsmoking habit were the main risk factors. Main diagnoses to the entrance:heart failure and unstable angina (24,8% and 25,2%, respectively). The atrialfibrillation was the most frequent (54,5%) arrhythmia, followed by atrioventricularblockade (25,2%). Anti-arrhythmic drugs were used as therapeuticmodality in 39,6%. Amiodarona was the most used medication. Eight patientsunderwent electrical cardioversion and permanent pacemaker were implantedin 31 patients. Eight patients died during the hospitalization (3,6%).The most frequent complication was cardiogenic shock.Conclusions The 16% of entered patients suffer from cardiac arrhythmias and dysfunctionof the conduction system. Atrial fibrillation was diagnosed in half of the patients.